Event-Shape-Dependent Analysis of Charm–Anticharm Azimuthal Correlations in Simulations - Anikó Horváth; Eszter Frajna; Róbert Vértesi (Universe, 2023)
In high-energy collisions of small systems, by high-enough final-state multiplicities, a collective behaviour is present that is similar to the flow patterns observed in heavy-ion collisions. Recent studies connect this collectivity to semi-soft vacuum-QCD processes. Here we explore QCD production mechanisms using angular correlations of heavy flavour using simulated proton-proton collisions at <semantics><msqrt>s</msqrt>=13</semantics> TeV with the PYTHIA8 Monte Carlo event generator. We demonstrate that the event shape is strongly connected to the production mechanisms. Flattenicity, a novel event descriptor, can be used to separate events containing the final-state radiation from the rest of the events.